Lao Qida-ийн хятад эхийн хэлний онцлог: Linguistic Features in the Chinese Original of Lao Qida - L., Manaljav; T., Otgontuul (Mongolian Journal of Foreign Languages and Cultures, 2023)
In this paper the objective is to show the peculiarities of the Chinese language of Lao Qida (or Nogeldai), the book was compiled during the period of the Mongolian Yuan Dynasty. The book was used as a textbook for teaching of foreign languages in Korea during Koryo Dynasty (1392-1910). Later on the Mongolian, Manchurian and other versions of the book have appeared. The main distinctive feature of the language of the book is the use of the colloquial Chinese language. This article describes some phonological, lexical and grammatical peculiarities of the Chinese language of Lao Qida. Our team of philologists is conducting a comparative study the Chinese, Mongolian and Manchurian versions of Lao Qida and the results of the study will be published within the framework of the project.